Hubungan Kecerdasan Emosi Dengan Kecenderungan Pemaafan Pada Remaja Akhir yang Mengalami Putus Cinta - Jasseline Kosasih; Carolin Sharen Shantyana Sipakkar; Flinser Dachi; Nurvica Sari; Rina Mirza (Jayapangus Press, 2026)
This study aimed to examine the relationship between emotional intelligence and the tendency toward forgiveness among late adolescents who have experienced romantic breakups at the Faculty of Psychology, Universitas Prima Indonesia. The research hypothesis proposed a positive relationship between emotional intelligence and the tendency toward forgiveness. A quantitative method with a correlational design was employed. The participants consisted of 142 students aged 18–21 years who had experienced a romantic breakup, selected using purposive sampling. The research instruments included an emotional intelligence scale and a forgiveness scale in Likert format. Data analysis was conducted using Pearson Product Moment correlation. The results indicated a significant positive relationship between emotional intelligence and the tendency toward forgiveness (r = 0.388; p < 0.05), with an effective contribution of 15.10%. These findings suggest that higher levels of emotional intelligence among late adolescents are associated with a greater tendency to forgive after experiencing a romantic breakup. The results of this study are important as a basis for developing psychological interventions focused on enhancing emotional intelligence to support the psychological well-being of late adolescents.